Kaposiform Hemangioendothelioma in Adolescent-Onset Scoliosis: A Case Report and Review of Literature. (7th February 2020) - Kim, Junho; Kim, Yeon Ho; Kim, Hyoungmin; Chang, Bong-Soon; Lee, Choon-Ki; Chang, Sam Yeol
Abstract : Background and Objectives. Kaposiform hemangioendothelioma (KHE) is a vascular tumor of very low incidence, which occurs mostly in children and infants. The tumor is recognized for its locally aggressive, yet rarely metastatic behavior. It may cause consumptive coagulopathy known as Kasabach-Merritt phenomenon. We report a distinctive case, where an 11-year-old boy is presented with progressive thoracolumbar scoliosis without any symptom or neurological sign. Case Report. The patient underwent spinal deformity correction via posterior pedicle screw instrumentation and fusion, along with tumor biopsy. The pathology report confirmed KHE. The patient did not show a prominent progression of scoliosis after the surgery without any further treatments. Conclusions . Many of scoliotic patients do not have any apparent cause, thereby regarded as idiopathic scoliosis. The presented case is where kaposiform hemangioendothelioma is likely to be linked to the patient's scoliosis. We demonstrate the possibility of secondary scoliosis should always be kept in mind of orthopaedic doctors. We also conclude that secondary scoliosis does not show exacerbation after growth completion.